SCHEDULING PLANNING SOYBEAN COMMODITY DISTRIBUTION ACTIVITIES AT CV XYZ USING DISTRIBUTION REQUIREMENT PLANNING (DRP) METHOD - Jilan Amarla Diwani; Iphov Kumala Sriwana; Nia Novitasari (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
CV XYZ is a company engaged in the distribution of soybean commodities, located in Tangerang Regency. The company distributes its products to five retail outlets across the Jabodetabek area using two operational vehicles. Currently, CV XYZ faced issues with distribution scheduling due to the lack of a fixed policy, leading to occasional increases in delivery frequencies caused by insufficient stock and an inefficient existing scheduling system. As a result, the fulfillment rate of retail demands only reached 93% of the company’s target of 99%, creating a 6% gap that the company aims to address. To resolve this issue, a new distribution scheduling plan was developed using the Distribution Requirement Planning (DRP) method. Distribution Requirement Planning (DRP) method consists of four stages: first Netting for the process of calculating the amount of net requirements, second Lotting for the process of calculating the ideal order quantity, third Offsetting to determine the order plan, and finally the fourth explosion for the process of calculating gross requirements in distribution. The results of the new plan show an increase in the fulfillment rate of retail demands to 99.8%. Additionally, total distribution costs were successfully minimized, decreasing from Rp 593,980,120 to Rp 551,934,498, resulting in a saving of Rp 42,045,622 or approximately 7% of the previous total distribution costs. Keywords: inventory, scheduling, distribution, distribution requirement planning (DRP)